A snapshot of the global drinking water virome: Diversity and metabolic potential vary with residual disinfectant use. (30th June 2022) - Hegarty, Bridget; Dai, Zihan; Raskin, Lutgarde; Pinto, Ameet; Wigginton, Krista; Duhaime, Melissa
Highlights: Viral sequences were mined from published drinking water metagenomes. Environmental and study-specific factors shape drinking water viruses. Lower viral diversity observed in drinking water with residual disinfectants. Drinking water viruses carry oxidative and nitrogen stress related genes. Abstract: Viruses are important drivers of microbial community ecology and evolution, influencing microbial mortality, metabolism, and horizontal gene transfer. However, the effects of viruses remain largely unknown in many environments, including in drinking water systems. Drinking water metagenomic studies have offered a whole community perspective of bacterial impacts on water quality, but have not yet considered the influences of viruses. In this study, we address this gap by mining viral DNA sequences from publicly available drinking water metagenomes from distribution systems in six countries around the world. These datasets provide a snapshot of the taxonomic diversity and metabolic potential of the global drinking water virome; and provide an opportunity to investigate the effects of geography, climate, and drinking water treatment practices on viral diversity. Both environmental conditions and differences in sample processing were found to influence the viral composition. Using free chlorine as the residual disinfectant was associated with clear differences in viral taxonomic diversity and metabolic potential, with significantly fewer viral populations and less even viral community structures than observed in distribution systems without residual disinfectant. Additionally, drinking water viruses carry antibiotic resistance genes (ARGs), as well as genes to survive oxidative stress and nitrogen limitation. Through this study, we have demonstrated that viral communities are diverse across drinking water systems and vary with the use of residual disinfectant. Our findings offer directions for future research to develop a more robust understanding of how virus-bacteria interactions in drinking water distribution systems affect water quality. Graphical abstract: Image, graphical abstract